2022
DOI: 10.1080/02626667.2022.2072220
|View full text |Cite
|
Sign up to set email alerts
|

Error propagation of climate model rainfall to streamflow simulation in the Gidabo sub-basin, Ethiopian Rift Valley Lakes Basin

Abstract: This study assesses bias error of rainfall from climate models and related error propagation effects to simulated streamflow in the Gidabo sub-basin, Ethiopia. Rainfall is obtained from a combination of four global and regional climate models (GCM-RCMs), and streamflow is simulated by means of the Hydrologiska Byråns Vattenbalansavdelning (HBV-96) rainfall-runoff model. Five bias correction methods were tested to reduce the rainfall bias. To assess the effects of rainfall bias error propagation, percent bias (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…This reduction may be attributed to mitigated cumulative error propagation stemming from the incorporation of predicted δ 2 H and δ 18 O values influenced by various climatic and spatial variables. Many studies have also indicated that the error propagation will cause a larger bias in hydrological model simulations [47,48].…”
Section: What Are the Differences Between The Three Models?mentioning
confidence: 99%
“…This reduction may be attributed to mitigated cumulative error propagation stemming from the incorporation of predicted δ 2 H and δ 18 O values influenced by various climatic and spatial variables. Many studies have also indicated that the error propagation will cause a larger bias in hydrological model simulations [47,48].…”
Section: What Are the Differences Between The Three Models?mentioning
confidence: 99%